2020
DOI: 10.1080/13600818.2020.1818714
|View full text |Cite
|
Sign up to set email alerts
|

Beyond ownership: women’s and men’s land rights in Sub-Saharan Africa

Abstract: Advancing women's land rights is a priority for the international development agenda. Little consensus exists, however, on which rights should be monitored and reported, especially in Sub-Saharan Africa where individual property rights and customary tenure regimes coexist and where much agricultural land remains unregistered. In such contexts, data collected on land ownership may provide only a limited complete picture of women's and men's land rights. While some surveys collect information on women's land own… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 23 publications
4
44
0
Order By: Relevance
“…Lusasi and Mwaseba (2020) showed that men owned most land while women accessed land through fathers, husbands and sons. As a rule, Slavchevska et al (2021) demonstrated that land possession by women in sub-Saharan Africa is constrained. It was observed among women that more educated ones are more selfreliant and like to have self-property rights, hence acquire their own territory.…”
Section: Relationship Between Gender Access To Land and Creditmentioning
confidence: 99%
See 1 more Smart Citation
“…Lusasi and Mwaseba (2020) showed that men owned most land while women accessed land through fathers, husbands and sons. As a rule, Slavchevska et al (2021) demonstrated that land possession by women in sub-Saharan Africa is constrained. It was observed among women that more educated ones are more selfreliant and like to have self-property rights, hence acquire their own territory.…”
Section: Relationship Between Gender Access To Land and Creditmentioning
confidence: 99%
“…Also, Anderson et al (2021) confirm a disparity in admittance to farmland by women. Less than 15% of agricultural landholders are women and 85% are men worldwide (Slavchevska et al, 2021). In Africa, women own under 1% of the agricultural land (Lusasi and Mwaseba, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this spirit, Kilic and Moylan (2016) distinguish between reported owners, economic owners, documented owners and holder of various bundles of rights. These differing ownership and use rights do not necessarily fall together (Slavchevska et al 2017;Doss et al 2020). 6 The DHS questions that were added to the 6 th round, capture a concept closest to that of reported ownership but cannot distinguish between different forms of ownership or provide information about the security of ownership.…”
Section: Dhs Data On Women's and Men's Property Ownershipmentioning
confidence: 99%
“…Instead, they continue to grow staple grain crops, mostly for home consumption. But men who remain withdraw labor from nonfarm work without significantly increasing their labor supply in agriculture (Slavchevska et al 2020a). Similarly, in Ethiopia, male out-migration increases women's labor allocations to agricultural activitiesthough without increasing their decision-making in agriculture (Ramos et al 2020).…”
Section: Gender and Rural Transformation Katrina Kosec Cheryl Doss mentioning
confidence: 99%